2004
DOI: 10.1128/jcm.42.12.5624-5635.2004
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Evolution of Medical Species of Candida and Related Taxa: a Multigenic Analysis

Abstract: Hemiascomycetes are species of yeasts within the order Saccharomycetales. The order encompasses disparate genera with a variety of life styles, including opportunistic human pathogens (e.g., Candida albicans), plant pathogens (e.g., Eremothecium gossypii), and cosmopolitan yeasts associated with water and decaying vegetation. To analyze the phylogeny of medically important species of yeasts, we selected 38 human pathogenic and related strains in the order Saccharomycetales. The DNA sequences of six nuclear gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
110
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 43 publications
11
110
0
2
Order By: Relevance
“…For example, there is substantial evidence that within the Ascomycota phylum, the Pezizomycotina and Saccharomycotina subphyla are sister groups (Fitzpatrick et al 2006;Kuramae et al 2006;Liu et al 2009;Philippe et al 2004;Robbertse et al 2006). However, there is conflicting evidence to suggest that the Taphrinomycotina and Saccharomycotina are sister clades (Baldauf et al 2000;Bullerwell et al 2003;Diezmann et al 2004). Similarly within the Basidiomycota phylum, a consensus regarding the phylogenetic relationships among the Ustilagomycotina, Pucciniomycotina, and Agaricomycotina subphyla is not yet available (Begerow et al 2004;Hibbett et al 2007;James et al 2006b).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, there is substantial evidence that within the Ascomycota phylum, the Pezizomycotina and Saccharomycotina subphyla are sister groups (Fitzpatrick et al 2006;Kuramae et al 2006;Liu et al 2009;Philippe et al 2004;Robbertse et al 2006). However, there is conflicting evidence to suggest that the Taphrinomycotina and Saccharomycotina are sister clades (Baldauf et al 2000;Bullerwell et al 2003;Diezmann et al 2004). Similarly within the Basidiomycota phylum, a consensus regarding the phylogenetic relationships among the Ustilagomycotina, Pucciniomycotina, and Agaricomycotina subphyla is not yet available (Begerow et al 2004;Hibbett et al 2007;James et al 2006b).…”
Section: Introductionmentioning
confidence: 97%
“…1, 2, 3, and 4). Until recently the phylogenetic relationships between these three subphyla were uncertain with some analyses placing Saccharomycotina and Taphrinomycotina as sister clades (Baldauf et al 2000;Diezmann et al 2004) while others inferred a sister group relationship between Pezizomycotina and Saccharomycotina (Fitzpatrick et al 2006;Kuramae et al 2006;Philippe et al 2004;Robbertse et al 2006). Recently a comprehensive phylogenomic analysis of 113 nuclear genes by Liu et al (2009) has shown that the Taphrinomycotina are a monophyletic clade and branch as a sister group to a (Pezizomycotina, Saccharomycotina) clade.…”
Section: Phylogenetic Relationships Among the Ascomycotamentioning
confidence: 99%
“…are also important pathogens in dogs, being related to: urinary infections [32], endophthalmitis [26], cutaneous lesions [28], and systemic infections [6]. The group with the most rel- [13,37].…”
Section: Introductionmentioning
confidence: 99%
“…The actin gene ACT1 and the elongation factor 2 gene EF2 were amplified with KOD FX polymerase (Toyobo Co.) using the primers ACT1 (59-TACCCAATTGAACACGGTAT-39) and ACT2 (59-TCTGAATCTTTCGTTACCAAT-39) for ACT1 and EFIIF1 (59-AAGTCTCCAAACAAAGCATAAC-39) and EFIIR2 (59-GGGAAA-GCTTGACCACCAGTAGC-39) for EF2. PCR was performed according to the method described by Diezmann et al (2004). The PCR products were purified with AMPure (Agencourt Bioscience Co.), according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%